INTEGRATED LESSONS OF RUSSIAN AS A FOREIGN LANGUAGE AT THE KARAKALPAK SCHOOL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article reveals the role of integrated lessons of Russian as a foreign language, focused on the development of the cognitive potential of students.